PREPAREDNESS FOR DISASTER RISK MANAGEMENT (DRM), CASE STUDIES: KELANTAN FLOOD, MALAYSIA - HASSAN, MOHD SAYUTI; ABDUL JAFFAR, MURSHIDAH; ABDULAMEER, SHAHAD KHALDOON; MOHD RADZI, SITI FAIRUZ; KANASAN, VISHANTHINI (Advances in Social Sciences Research Journal, 2020)
In accordance to the massive flash floods that hit Eastern part of Malaysia, which is mostly Kelantan state, a conference was held to explore ideas and sustainable solutions for the disaster. This paper describes one output of the five pillars of disaster management cycle that is “Preparedness” in Disaster Risk Management for Sustainable Development (DRM-SD) model, which was developed by Centre for Global Sustainability Studies (CGSS) Universiti Sains Malaysia (USM). The purpose is to come out with possible solutions and steps to be taken to mitigate the flood disaster while preparing for any possibilities. The method used for the conference is The Town Hall-World Café concept. Over 225 possible solutions are produced in two days in which the conference is conducted. Included in this paper are the recommendations that were found and the organizations which are responsible for the act.